Design and development of an small-scale ocean wave energy converter - Amlan @ Amran, Muhammad Nor Akhmar (2025)
The wind that blows across the ocean's surface creates waves, which have a vast amount of potential energy. Ocean wave energy, the most plentiful sustainable power source, has a high energy density, which makes it a desirable option for supplying the growing annual need for electricity. But there is still a lot of work to be done to consistently and efficiently harness this energy. The aim of this project is to design, build, and test a cost- effective, long-lasting, and efficient prototype small- scale ocean wave energy converter (WEC). A complete strategy that includes the optimization of power electronics, materials selection, and hydraulic systems will be used to accomplish this. A thorough examination of the prototype's performance will likewise be carried out as part of the project. This evaluation will cover its capacity to transform ocean wave energy into electrical power, its ability to operate in challenging oceanic conditions, and its affordability in comparison to current WEC designs. An dependable and sustainable power source is what this initiative aims to achieve, which will decrease reliance on conventional energy sources and contribute to climate change. Ocean wave energy will eventually be widely adopted as a renewable energy source thanks to the project's results, which will offer insightful information for the creation of more dependable and efficient WEC designs